Periodisasi Islam Nusantara Sejak Era Walisongo: Periodization of Indonesian Islam Since the Walisongo Era - Chotib, Muhammad Qurrotul Ainul; ., Ayatullah (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2024)
This study aims to explore the foundations of the Islam Nusantara concept, introduced by Nahdlatul Ulama (NU) at its 33rd Congress in Jombang in 2015. The Islam Nusantara concept remains a relevant issue for discussion, as some groups within the Indonesian Muslim community continue to reject it due to a lack of comprehensive understanding, viewing it as contradictory to the teachings of Islam brought by the Prophet Muhammad (PBUH). Therefore, the research questions addressed in this study are: How does Islam Nusantara establish its doctrinal and scholarly basis with regard to the teachings of the Walisongo? And how have the Islamic teachings propagated by the Walisongo been preserved to this day? This study employs library research through a historical approach encompassing four stages: heuristics, source criticism, interpretation, and historiography. The method used is content analysis of primary and secondary data sources. The findings of this study indicate that Islam Nusantara, as introduced by NU, is not a concept without foundation. This study affirms that its foundation is rooted in the Islamic traditions of the Walisongo. This is evident from the scholarly framework of Islam Nusantara, which consistently follows a particular school of thought (madhhab) and is based on the principles of Ahlussunnah wal Jama'ah (Aswaja). Furthermore, the core teachings of Islam Nusantara—such as moderation (Tawassuth), balance (Tawaazun), fairness (I'tidal), and tolerance (Tasamuh)—represent an effort to actualize the Islamic teachings passed down by the Walisongo within the Islam Nusantara concept.